Comprehensive characterisation of sewage sludge for thermochemical conversion processes - Based on Singapore survey - Chan, Wei Ping (2017)
Recently, sludge attracted great interest as a potential feedstock in thermochemical conversion processes. However, compositions and thermal degradation behaviours of sludge were highly complex and distinctive compared to other traditional feedstock led to a need of fundamental research on sludge. Comprehensive characterisation of sludge specifically for thermochemical conversion was carried out for all existing Water Reclamation Plants in Singapore. In total, 14 sludge samples collected based on the type, plant, and batch categorisation. Existing characterisation methods for physical and chemical properties were analysed and reviewed using the collected samples. Qualitative similarities and quantitative variations of different sludge samples were identified and discussed. Oxidation of inorganic in sludge during ash forming analysis found to be causing significant deviations on proximate and ultimate analysis. Therefore, alternative parameters and comparison basis including Fixed Residues (FR), Inorganic Matters (IM) and Total Inorganics (TI) were proposed for better understanding on the thermochemical characteristics of sludge.